Yendegaia Rockshelter, the First Rock Art Site on Tierra del Fuego Island and Social Interaction in Southern Patagonia (South America) - Gallardo, Francisco; Cabello, Gloria; Sepulveda, Marcela; Ballester, Benjamin; Fiore, Danae; Prieto, Alfredo (My University, 2023)
Through our research at Bahia Yendegaia on the Beagle Channel in southernmost Patagonia-the ancestral territory of the Yagan people-we discovered the first rock art site on Tierra del Fuego Island. The geometric visual images found at Yendegaia Rockshelter present motifs and compositions analogous to those recorded at other sites on the southern archipelago associated with the marine hunter-gatherer tradition. They also show graphic similarities to the rock art paintings attributed to terrestrial hunter-gatherer populations from the Pali Aike volcanic field, located on the north side of the Strait of Magellan in mainland Patagonia. Both, however, display quantitative differences, which suggest that they emerged from different visual traditions but from the same field of graphic solutions. Navigational technology enabled the canoe-faring Fuegian people to have long-distance mobility and to maintain a flow of social information mediated via visual imagery expressed in material forms, such as rock art and expressions of portable art. Ethnohistoric reports suggest a cooperative social interaction more than a competitive one. This cooperative social dynamic would have been necessary for the survival of marine societies in the harsh environmental conditions characteristic of the southern part of south Patagonia.
Keywords: rock painting; fuegian archipelago; southern patagonia; social interaction; information flows